The territoriality paradigm in cultural tourism - Jansen-Verbeke, Myriam (Turyzm/Tourism, 2009)
A typical geographers' approach to tourism is to emphasise the analysis of spatial flows and space uses and the synthesis of territorial coherence between people, place and product. The renewed interest in the territorial aspects of tourism can be seen as a response to globalisation on the one hand and the search for unique, authentic and grass-rooted experience on the other. In recent tourism studies the focus and methods shift from a description of patterns to the analysis of processes of change that are induced by tourism (touristification). Understanding the forces that are transforming cultural landscapes (urban and rural) into tourismscapes is a crucial condition for visionary planning and responsible management of regions and places. Some reflections on the future research agenda in geo-tourism will be included.